Molecular Docking Study of Active Compounds in White Radish (Raphanus sativus L.) on Cyclooxygenase-2 (COX-2) Receptor as an Anti-Inflammatory Agent - Abdul Rahman Lubis; Wahyu Yuliana Solikah; Daru Estiningsih; Nurul Jannah (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2025)
Inflammation is a natural endogenous response to injury, infection, or external stimuli, and it plays a critical role in the pathogenesis of various diseases, including arthritis and osteoarthritis. Despite their effectiveness, the long-term use of nonsteroidal anti-inflammatory drugs (NSAIDs) often leads to several adverse effects, particularly gastrointestinal complications. Therefore, it is crucial to explore safer alternative therapies. This study aimed to evaluate the potential of bioactive compounds found in white radish (Raphanus sativus L.) as alternative anti-inflammatory agents using in silico molecular docking analysis against the cyclooxygenase-2 (COX-2) enzyme. Molecular docking simulations were performed using AutoDock Vina software, with the COX-2 structure obtained from the Protein Data Bank (PDB ID: 4PH9). The docking results indicated that glucoraphanin and squalene exhibited strong binding affinities with binding energies of –8.53 kcal/mol and –8.62 kcal/mol, respectively. Glucoraphanin was found to form hydrogen bonds with key active site residues similar to the interaction observed with ibuprofen, a standard NSAID. Meanwhile, squalene predominantly engaged in hydrophobic interactions with the enzyme. These findings suggest that glucoraphanin and squalene have the potential to act as effective COX-2 inhibitors and could serve as safer alternatives to conventional NSAIDs. However, further in vitro and in vivo studies are essential to validate their therapeutic potential and safety profiles.